Increasing Managerial Performance through The Use of Information Technology and Decentralization Characteristics of the Management Accounting System - Ligar Hardika, Andhika; Nur Fathonah, Andina; Darrini, Anni; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to discuss the use of information technology, decentralization of the characteristics of accounting systems, and managerial management of state-owned enterprises. This type of research uses descriptive verification. The population of all managers of state-owned enterprises in the city of Bandung. Sampling uses a sampling of 68 middle-level managers. The study uses path analysis by processing statistical data using multiple regression analysis. Data were analyzed using IBM SPSS Ver 20. This study found that the use of information technology and decentralization applied to the characteristics of management accounting systems and managerial performance. This research provides insights about top management to improve performance in developing information technology and delegating authority and responsibility to provide solutions to improve managerial performance.